Pengaruh Kompetensi Kepribadian Guru PAI terhadap Akhlak Setingkat Sekolah Menengah Pertama - Niswatin, Khoirun; Darmawan, Didit (Lembaga Yasin AlSys, 2025)
This research is motivated by the morality of students which is increasingly worrying and disturbing. Morality or morality is the most important part of everyday life because morality is used as a sign of good or bad someone. This study aims to analyze the influence of Islamic Religious Education teacher personality competence on morality at the Junior High School level. The research method used is a qualitative method with a literature review approach to explore the influence of Islamic Religious Education teacher personality competence on morality. The results of the study stated that Islamic Religious Education teacher personality competence has a significant effect on the morality of students at the Junior High School level. The conclusion of this study is that teacher personality competence is a factor that determines the closeness of a teacher to his students. A teacher's personality can be seen from his behavior and actions in fostering and educating students. A teacher's behavior and actions are the most important factors in a teacher's personality competence.